GA Houses 184. - Futagawa, Yoshio; Saito, Hitomi; Nakamura, Akiyo (Tokyo : A.D.A. Edita Tokyo Co., Ltd., 2022)
Christian Kerez - House Okamura ; Andra Matin - Y&S Residence ; Andra Matin - Ma Residence ; Andra Matin - Omah Jati ; João Mendes Ribeiro - Chestnut House ; João Mendes Ribeiro - Arruda Dos Vinhos House ; Yo Shimada - House in Shirakawa ; Suzuko Yamada - Miyazaki ; Chris Bligh + Sonia Graham - Live Work Share House ; Makoto Tanijiri + Ai Yoshida / Suppose Design Office - House in Ota
boek